2013
DOI: 10.1152/ajprenal.00174.2013
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid mutations in the caldesmon COOH-terminal functional domain increase force generation in bladder smooth muscle

Abstract: Caldesmon (CaD), a component of smooth muscle thin filaments, binds actin, tropomyosin, calmodulin, and myosin and inhibits actin-activated ATP hydrolysis by smooth muscle myosin. Internal deletions of the chicken CaD functional domain that spans from amino acids (aa) 718 to 731, which corresponds to aa 512-530 including the adjacent aa sequence in mouse CaD, lead to diminished CaD-induced inhibition of actin-activated ATP hydrolysis by myosin. Transgenic mice with mutations of five aa residues (Lys(523) to Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…S2 ). In this context, it is interesting to note that point mutations in the C terminus of CaD in a mouse model, which did not lower CaD expression levels but interfered with the inhibition on cross-bridge cycling, increased force ( Deng et al, 2013 ) similar to the observed increased force in HETs in our study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…S2 ). In this context, it is interesting to note that point mutations in the C terminus of CaD in a mouse model, which did not lower CaD expression levels but interfered with the inhibition on cross-bridge cycling, increased force ( Deng et al, 2013 ) similar to the observed increased force in HETs in our study.…”
Section: Discussionsupporting
confidence: 77%
“…In visceral smooth muscles, l-CaD expression was up-regulated, which may compensate for the loss of h-CaD ( Guo et al, 2013 ). In another mouse model, the introduction of five point mutations within the C terminus of CaD, which encompassed the ATPase inhibitory determinants, resulted in a lethal phenotype in homozygous but not heterozygous (HET) mice ( Deng et al, 2013 ). Adult HET mice displayed nonvoiding contractions during urinary bladder filling.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a model with homozygous loss of h-caldesmon, the loss is shown not to be lethal [28,29]. Another mouse model with mutations targeting a functional domain in both isoforms is lethal as a homozygote but reproduces normally as a heterozygote [30]. The severe cardiovascular defects are not described in Cald1-deficient mice, although the underlying causes of pre-and postnatal lethality are not fully understood [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…This action of caldesmon should be important to maintain bladder relaxation during filling. Recently, it has been demonstrated that mice with mutations in the caldesmon gene that encompass the ATPase inhibitory domain show non‐voiding contractions during awake cystometry . However, it is not yet clear if this effect is likely to underlie pathological increases of bladder dysfunction as the action of caldesmon on actin–myosin interaction is only observed at basal levels of MLC 20 phosphorylation.…”
Section: The Potential Role Of Contractile Proteins In Contributing Tmentioning
confidence: 99%